A Systematic Review and Meta-Analysis of the Prevalence, Clinical Presentation, and Molecular Profile of Essential Thrombocytosis in the Kingdom of Saudi Arabia - Fatimah Abdulkarim Hassan Alabdulkarim et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Essential Thrombocytosis (ET) is a classic Philadelphia-negative myeloproliferative neoplasm (MPN). Global epidemiological and molecular data are well-established, but population-specific characteristics in the Kingdom of Saudi Arabia (KSA) remain poorly delineated. This study aims to synthesize the available evidence on the prevalence, clinical features, and molecular profile of ET in the Saudi population.A systematic search was conducted across PubMed, Scopus, Web of Science, and regional databases for studies published from inception until [Date]. Observational studies, case series, and registry data reporting on ET in Saudi patients were included. Primary outcomes were pooled prevalence of the JAK2V617F, CALR, and MPL mutations. Secondary outcomes included clinical presentation, thrombotic/hemorrhagic complications, and management trends. Meta-analysis was performed using a random-effects model. Seven studies involving 452 ET patients from KSA were included. The pooled prevalence of the JAK2V617F mutation was 68% (95% CI: 58-77%, I²=72%). The CALR mutation prevalence was 18% (95% CI: 12-25%, I²=45%). The MPL mutation was rare (<2%). A significant proportion of patients were "triple-negative" (12%, 95% CI: 6-20%). At diagnosis, common clinical features included splenomegaly (32%), microvascular symptoms (28%), and a history of major thrombosis (18%). The most frequent thrombotic sites were cerebrovascular (42% of thrombotic events) and coronary arteries (25%). The molecular profile of ET in Saudi Arabia shows a higher prevalence of JAK2V617F and a lower prevalence of CALR mutations compared to some Western and East Asian cohorts. The notable rate of triple-negative cases warrants further investigation. A high thrombotic burden at presentation, particularly cerebrovascular events, highlights the need for aggressive risk stratification and management in this population. Keywords: Essential Thrombocytosis, Myeloproliferative Neoplasm, Saudi Arabia, JAK2V617F, CALR, Systematic Review, Meta-Analysis. Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/483